Pink Saris - Longinotto, Kim (Ginger Productions ; Vixen Films, 2010)
Coproduction: India, UK. Verzio FF Submission. Duration: 01:36:00 The Gulabi Gang (a.k.a. the “Pink Gang”) is an active group of female vigilantes from the "Untouchables" caste in northern India, who have resisted being condescended to as the lowest social class and who are now fighting against social injustices and domestic abuse towards women. "If you're shy, you'll die," preaches Sampat Pal Devi, the leader of the Gulabi Gang, and who for the past 20 years has been battling for women's rights in northern India. The film follows her on her journey as she visits many families, giving them a lash of her sharp tongue if she discovers that they have beaten their daughter or kicked her out of the house. She approaches groups of men in a raging fury, seeking compensation, and gives fiery advice to the female onlookers. Sampat believes, that the problems are fundamentally caused by the caste system and the religion adhered to by the lowest caste, the "Untouchables," and she does everything in her power to break up the entrenched traditions. It is only when Sampat's husband starts to have enough of his wife's celebrity status that the film shows her vulnerable side for the first time.